EVALUASI PERFORMANSI THROUGHPUT/DELAY PADA MAC PROTOKOL IEEE 802.11 - Taqwa, Ahmad
Abstract : It is difficult for users of any IEEE 802.11 Wireless LAN station to choose manually which mechanism of Distributed Coordination Function (DCF) should be applied to the station in certain condition of network. At the IEEE 802.11 Wireless LAN, DCF is a fundamental mode to support best-effort delivery services in a Basic Service Set (BSS). The DCF defines a basic-access mechanism for packet transmission: Carrier Sense Multiple Access with Collision Avoidance (CSMAICA) and Request to Send / Clear to Send (RTS/CTS) as optional mechanism. The RTS/CTS function is used to reserve channel by transmitting a short control frame before transmitting a data packet. The use of RTS/CTS will make sense for services application with long packet to decrease collision probability. Although RTS/CTS has an advantage for preventing the collision, but it needs additional time for hand shaking. The IEEE 802.11 expresses that RTS/CTS will be used if the packet duration is longer than RTS threshold parameter. In this paper we will evaluate and show the way how to choose DCF mechanism that should be applied in a network, and how to optimize its performance based on threshold parameter.